Construction of an El Tor Biovariant Vibrio cholerae Strain Capable of Type II Cholera Toxin Hyperproduction and Determining the Optimal Conditions for the Production of This Protein - A. A. Goryaev; E. Yu. Shchelkanova; Yu. V. Lozovsky; I. V. Touchkov; N. I. Smirnova (Проблемы особо опасных инфекций, 2008)
Introduction of Tn5-Mob (KmR) transposon into the chromosome of the toxinogenic V. cholerae strain MAK757 El Tor biovar was shown to result in the emergence of insertion mutants containing an altered genome of CTXφ prophage. The reorganization ofthe latter was expressed in the deletion of four genes, zot, асе, сер, orfU, however,its ctxAB operon coding for the synthesis of type II cholera toxin being still retained. This change in the CTXφ prophage has lead to as high as 200 fold greater levels of production of this protein by MAK757clones chr::Tn5-Mob (Km') Tox++. A single clone with the highest cholera toxin biosynthesis levels (42.0-45.0 |xg/ml) was selected among the insertion mutants Km" Tox+and designated as KM234. The optimal conditions for culturing the KM234 construct were fitted to provide for the highest cholera toxin elaboration by the cells. The El Tor biovar V. cholerae strain KM234 thus constructed was shown to be a stable and efficient type II cholera toxin overproducing strain promising to be applied in the industrial production of this protein routinely used to manufacture the preparations for cholera diagnosis and prophylaxis.